2014
DOI: 10.1007/s00277-014-2137-6
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent chemoradiotherapy followed by l-asparaginase-containing chemotherapy, VIDL, for localized nasal extranodal NK/T cell lymphoma: CISL08-01 phase II study

Abstract: We conducted a phase II trial of concurrent chemoradiotherapy (CCRT) followed by 2 cycles of L-asparaginase-containing chemotherapy for patients who were newly diagnosed with stages IE and IIE nasal extranodal NK/T cell lymphoma (ENKTL). CCRT consisted of 40-44 Gy of radiotherapy with weekly administration of 30 mg/m(2) of cisplatin for 4 weeks. Two cycles of VIDL (etoposide (100 mg/m(2)), ifosfamide (1,200 mg/m(2)), and dexamethasone (40 mg) from days 1 to 3, and L-asparaginase (4,000 IU/m(2)) every other day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
93
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(103 citation statements)
references
References 21 publications
7
93
2
1
Order By: Relevance
“…To avoid a delay in RT, several prospective trials applied concurrent chemoradiotherapy, with reported 5-year OS rates of 60% to 73%. [37][38][39][40] In this large cohort of early-stage patients, the 5-year OS rates after RT alone for the low-risk group (88.8%) or after sequential RT and CT for the high-risk group (72.2%) were superior or comparable to other recent small series of concurrent, sequential, or "sandwich" CT and RT, regardless of the CT regimen. [36][37][38][39][40][41][42][43][44] Therefore, RT followed by optional CT offers the advantage of effective RT and has a more tolerable safety profile [4][5][6]15,16 and may reduce the risk of chemoresistance.…”
Section: Blood 17 September 2015 X Volume 126 Number 12 Risk-adaptementioning
confidence: 49%
“…To avoid a delay in RT, several prospective trials applied concurrent chemoradiotherapy, with reported 5-year OS rates of 60% to 73%. [37][38][39][40] In this large cohort of early-stage patients, the 5-year OS rates after RT alone for the low-risk group (88.8%) or after sequential RT and CT for the high-risk group (72.2%) were superior or comparable to other recent small series of concurrent, sequential, or "sandwich" CT and RT, regardless of the CT regimen. [36][37][38][39][40][41][42][43][44] Therefore, RT followed by optional CT offers the advantage of effective RT and has a more tolerable safety profile [4][5][6]15,16 and may reduce the risk of chemoresistance.…”
Section: Blood 17 September 2015 X Volume 126 Number 12 Risk-adaptementioning
confidence: 49%
“…32 A novel regimen containing L-asparaginase (SMILE) had a better effect than anthracycline-based chemotherapy. 33,34 The addition of radiotherapy for earlystage nasal cases yielded survival benefits. 35 Biomarkers associated with poor prognosis included the expression of p53 and p63, and high serum levels of interleukin-9, CXCL13, serum VEGF, and survivin.…”
Section: Modern Pathology (2016) 29 430-443mentioning
confidence: 99%
“…However, the relapse rates were high, ranging from 25 to 40 % [1,3]. Combined chemotherapy and radiotherapy typically as concurrent chemoradiotherapy [4][5][6], and sequential l-asparaginase-based chemotherapy and sandwiched radiotherapy [7,8] significantly decreased the relapse rates and improved the long-term overall survival and progression-free survival. Patients with disseminated disease showed very poor responses to conventional anthracycline-containing regimens.…”
Section: Introductionmentioning
confidence: 97%